1988
DOI: 10.1113/jphysiol.1988.sp016941
|View full text |Cite
|
Sign up to set email alerts
|

Maximum velocity of shortening related to myosin isoform composition in frog skeletal muscle fibres.

Abstract: SUMMARY1. The velocity of unloaded shortening (VI), the myofibrillar ATPase activity and the immunoreactivity to two monoclonal antibodies (A1 and A2) that were raised against the myosin heavy chains were studied in single fibres of the anterior tibialis muscle of Rana temporaria. VO was recorded for the fibre as a whole using the slacktest method. Myofibrillar ATPase activity was determined by means of a quantitative histochemical technique.2. A highly significant, direct relationship was found to exist betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
1
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(66 citation statements)
references
References 12 publications
3
61
1
1
Order By: Relevance
“…Collectively, segmental variations in MHC isoform expression (16,30) and the presence of polymorphic fibers that do not adhere to the sequential scheme (both under steady-state and transitional conditions) provide important pieces of evidence demonstrating that the genetic regulation of MHC isoform composition is sufficiently complex that it may not be simply described by the I7I/IIA7IIA7IIA/IIX7IIX7IIX/ IIB7IIB scheme. Does this mean that all fiber transitions do not adhere to this scheme?…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, segmental variations in MHC isoform expression (16,30) and the presence of polymorphic fibers that do not adhere to the sequential scheme (both under steady-state and transitional conditions) provide important pieces of evidence demonstrating that the genetic regulation of MHC isoform composition is sufficiently complex that it may not be simply described by the I7I/IIA7IIA7IIA/IIX7IIX7IIX/ IIB7IIB scheme. Does this mean that all fiber transitions do not adhere to this scheme?…”
Section: Discussionmentioning
confidence: 99%
“…A relation between shortening velocity and ATPase activity and MHC isoform composition has been found in studies performed on rat ventricular myocardium (Mercandier, Lompre, Wisnewsky, Samuel, Bercovici, Swinghedauw & Schwartz, 1981), rabbit single skinned muscle fibres (Reiser, Moss, Giulian & Greaser, 1985), avian single skinned fibres and frog muscle fibres (Edman, Reggiani, Schiaffino & te Kronnie, 1988). Recent studies, however, have shown a large variability in shortening velocity among mammalian fibres containing fast MHC .…”
Section: Introductionmentioning
confidence: 99%
“…Contractile speed, including the maximum velocity of fibre shortening and maximum rates of force development and relaxation, is governed by the kinetics of actinmyosin interaction and sarcoplasmic reticulum Ca 2+ release and reuptake (Briggs et al, 1977;Edman et al, 1988;Metzger and Moss, 1990;Gordon et al, 2000). Fibre type-specific expressions of the motor protein myosin (Edman et al, 1988;Bottinelli et al, 1991), and fibre type-related differences in Ca 2+ dynamics (Baylor and Hollingworth, 2003;Barclay, 2012) and contractile apparatus Ca 2+ sensitivity (Stephenson and Williams, 1981) mean that the mechanical output of whole muscle is also a function of fibre type composition (Harridge et al, 1996). The performance of skeletal muscle in functional terms, as either a powerful motor or brake, is ultimately dependent on both high contractile force and speed being effectively transferred to the skeletal system.…”
Section: Introductionmentioning
confidence: 99%